Diagnose on the most effective reading strategies used by fourth-year students from Licenciatura en Idioma Ingles Opción enseñanza, in reading printed academic texts on Readings and Conversations II academic year I-2012 at the Foreign Language Department at the Universidad de El Salvador - Aguilar Segura, Dorcas Elizabeth; Guerrero Trejo, Iliana Melissa; Mejía Martínez, Susana Ester; Salazar Murcia, Pedro Antonio; Ayala, Edgar Nicolás (San Salvador El Salvador : Universidad de El Salvador, 2013)
The purpose of this project is to diagnose the most used reading strategies applied by fourth-year students specifically at Readings and Conversation II from Licenciatura en Idioma Ingles Opción enseñanza. This study aims also to modify the Advanced Intensive English II syllabus to improve how reading strategies are taught to the Advanced Intensive English II students. This project will take place at the Foreign Language Department of the Universidad de El Salvador. The elements that take place in this project are as follow: first, the topic is stated as a brief introduction to give the reader a general idea what this research is about. Then, the general and the specific objectives are listed to identify the purpose of this investigation. After that, the justification is presented to describe the importance of this study; second, the theoretical framework is developed to provide deep information about previous literature that studies this topic in different scenarios. Third, the methodology is explained as a simple description of every single step that researchers followed to gather, process, and analyze data; deliberate sampling is used in this project. Forth, results are presented for the deliberate sampling and discussed in order to make more remarkable important findings. Then, a proposal to improve and renew the way reading strategies are taught in the Advance Intensive English II program. In the renew program one reading strategy is added at the beginning of each unit, so the teacher can explain a new reading strategy for each unit, this in order to improve students’ knowledge about reading strategies. Finally, the bibliography is listed to help readers to find a broad range of information sources about this topic.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliográfia : hojas 33-35
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza